Persepsi Guru PPPK terhadap Transparansi dalam Penilaian Kinerja di SMP Negeri 21 Palembang: Penilaian Kinerja Guru PPPK - Dwi Nur Kumalasari; Sri Rizki Amalia; Rani Darliana; Neta Dian Lestari; Ahmad Zulinto (STKIP Subang, 2025)
Assessment of PPPK Teachers’ Performance is an essential aspect in the education sector, particularly in ensuring objectivity, accountability, and the continuity of teachers’ professional development. This study aims to describe the perceptions of PPPK teachers at SMP Negeri 21 Palembang regarding the transparency in the performance appraisal process. The background of this research is based on the demands of the merit system and the need for transparency in criteria, procedures, and the utilization of performance appraisal results to prevent perceptions of unfairness or bias. The study employed a qualitative-descriptive approach using Likert-scale closed questionnaires and open-ended questionnaires administered to 33 PPPK teachers as respondents. The results indicate that teachers’ perceptions fall into the high category in aspects of procedural transparency, openness of HR administrative information, fairness and objectivity of assessment, as well as HR management accountability, with an average score of 4.18, categorized as high. The most positive perception appears in the aspect accountability and responsibility. However, some teachers still experience limited access to written performance appraisal results and insufficient in-depth feedback from evaluators. Other findings highlight that PPPK teachers expect strengthened transparency through digital information systems and more consistent explanation of indicators. Overall, the study concludes that HR administrative transparency has been implemented well but still requires improvements in documentation and openness of appraisal results in order to enhance motivation, trust, and the quality of teacher performance management in schools.